Treatment of hypertriglyceridemia with fenofibrate, fatty acid composition of plasma and LDL, and their relations to parameters of lipoperoxidation of LDL - Zeman, M; Zák, A; Vecka, M; Tvrzická, E; Romaniv, S; Konárková, M (Annals of the New York Academy of Sciences, 2002)
The purpose of this study was to determine oxidation and oxidability of VLDL and LDL in connection with changes in their composition and content of FA in LDL after treatment with fenofibrate in patients with HTG.
Keywords: hypertriglyceridemie; Humans; hypolipidemika; lidé středního věku; Female; Aged; dospělí; peroxidace lipidů; Fenofibrate; senioři; lidé; Hypertriglyceridemia; Adult; mastné kyseliny; lipoproteiny LDL; ženské pohlaví; Male; Middle Aged; Hypolipidemic Agents; Lipoproteins, LDL; fenofibrát; mužské pohlaví; Lipid Peroxidation; Fatty Acids